1998
DOI: 10.1002/(sici)1096-9861(19980302)392:1<115::aid-cne8>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Organization of ascending pathways to the forelimb area of the dorsal accessory olive in the cat

Abstract: The purpose of these experiments was to define the topography of cuneate and spinal projections to the forelimb representation in the rostral dorsal accessory olive (rDAO). We were interested in determining whether the spinal and cuneate inputs constitute a homogeneous afferent source, and whether there is evidence that they serve different functional roles. We were also interested in determining whether the somatotopy of rDAO is the result of a point-to-point projection from its afferent sources, or whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 60 publications
(116 reference statements)
2
38
0
Order By: Relevance
“…Roughly in parallel to the developing reduction of the suppression of the pyramidal tract response over time, also the climbing fiber field response evoked from the skin was reduced (peak reduction 94% ± 6% SD at 152 min) (Figure 7). This is in concert with that there are both excitatory and inhibitory connections from the cuneate to the IO (McCurdy et al, 1992, 1998). In contrast, the direct response evoked by the pyramidal tract was unaffected.…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…Roughly in parallel to the developing reduction of the suppression of the pyramidal tract response over time, also the climbing fiber field response evoked from the skin was reduced (peak reduction 94% ± 6% SD at 152 min) (Figure 7). This is in concert with that there are both excitatory and inhibitory connections from the cuneate to the IO (McCurdy et al, 1992, 1998). In contrast, the direct response evoked by the pyramidal tract was unaffected.…”
Section: Resultsmentioning
confidence: 79%
“…McCurdy et al (1992, 1998) found two ventral termination sites within the cuneate, one rostral, and one caudal, for the rubral fibers. Interestingly, in our case the suppression was most effective from sites located in the dorsal parts of the cuneate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations